2012
DOI: 10.3109/00365521.2012.661760
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the risk of celiac disease in children born small for gestational age: A sibling design perspective

Abstract: Our results support a causal association between SGA and CD risk in boys but not in girls, although the mechanisms underlying this difference are still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
(82 reference statements)
3
19
1
Order By: Relevance
“…It is worth noting that this study found no increased risk for CD in children diagnosed after the age of two (Table S1) . Other studies have also reported weak associations between paediatric CD and summer birth , and a US study found an association between spring birth and CD in boys diagnosed before 15 years of age . However, other studies have not found a significant association between birth season and CD .…”
Section: Season Of Birthcontrasting
confidence: 54%
See 2 more Smart Citations
“…It is worth noting that this study found no increased risk for CD in children diagnosed after the age of two (Table S1) . Other studies have also reported weak associations between paediatric CD and summer birth , and a US study found an association between spring birth and CD in boys diagnosed before 15 years of age . However, other studies have not found a significant association between birth season and CD .…”
Section: Season Of Birthcontrasting
confidence: 54%
“…The mechanism underlying this association is unknown, and although it is conceivable, we are not aware of any clear evidence suggesting that the CD pathogenesis differs for children diagnosed before or after the age of two. Secondly, some of the studies are from partly overlapping study populations .…”
Section: Season Of Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the standard design normally does not consider the existence of paired cases in the sample (e.g., siblings), which violate the assumption of independence of observations. In this context, family designs have been applied to population-based registries providing robust quasi-experimental analyses [25][30]. The idea behind family designs is to approximate a counterfactual situation by examining the effects of different exposures (for e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder has been associated with neonatal mortality and morbidities2 as well as with major medical problems across the life course, such as a higher risk of neurodevelopmental impairments,3 4 autism,5 schizophrenia,6 impaired cognitive function,7 coeliac disease in boys8 and reduced bone mass during early infancy,9 as well as Barrett's oesophagus and oesophagitis10 11 and others 12 13. Therefore, the identification of maternal and newborn characteristics (denominated as ‘risk factors’ in the rest of this work) associated with an increased risk for SGA is of obvious relevance in public health and preventive medicine.…”
Section: Introductionmentioning
confidence: 99%